Over-the-scope-clips versus standard treatment in high-risk patients with acute non-variceal upper gastrointestinal bleeding: a randomised controlled trial (STING-2). Issue 7 (23rd March 2022) - Meier, Benjamin; Wannhoff, Andreas; Denzer, Ulrike; Stathopoulos, Petros; Schumacher, Brigitte; Albers, David; Hoffmeister, Albrecht; Feisthammel, Jürgen; Walter, Benjamin; Meining, Alexander; Wedi, Edris; Zachäus, Markus; et al.
Abstract : Objective: Acute non-variceal upper gastrointestinal bleeding (NVUGIB) is managed by standard endoscopic combination therapy, but a few cases remain difficult and carry a high risk of persistent or recurrent bleeding. The aim of our study was to compare first-line over-the-scope-clips (OTSC) therapy with standard endoscopic treatment in these selected patients. Design: We conducted a prospective, randomised, controlled, multicentre study (NCT03331224 ). Patients with endoscopic evidence of acute NVUGIB and high risk of rebleeding (defined as complete Rockall Score ≥7) were included. Primary endpoint was clinical success defined as successful endoscopic haemostasis without evidence of recurrent bleeding. Results: 246 patients were screened and 100 patients were finally randomised (mean of 5 cases/centre and year; 70% male, 30% female, mean age 78 years; OTSC group n=48, standard group n=52). All but one case in the standard group were treated with conventional clips. Clinical success was 91.7% (n=44) in the OTSC group compared with 73.1% (n=38) in the ST group (p=0.019), with persistent bleeding occurring in 0 vs 6 in the OTSC versus standard group (p=0.027), all of the latter being successfully managed by rescue therapy with OTSC. Recurrent bleeding was observed in four patients (8.3%) in the OTSC group and in eight patients (15.4%) in the standard group (p=0.362). Conclusion: OTSC therapy appears to be superior to standard treatment with clips when used by trained physicians for selected cases of primary therapy of NVUGIB with high risk of rebleeding. Further studies are necessary with regards to patient selection to identify subgroups benefiting most from OTSC haemostasis. Trial registration number: NCT03331224 .